2014
DOI: 10.2134/jeq2014.02.0074
|View full text |Cite
|
Sign up to set email alerts
|

Copper and Zinc Speciation in a Biosolids-Amended, Semiarid Grassland Soil

Abstract: Abbreviations: DOC, dissolved organic carbon; HFO, hydrous ferric oxides; ICP-AES, inductively coupled plasma-atomic emission spectroscopy; OM, organic matter; SEM-EDXRA, scanning electron microscopy and energy-dispersive X-ray analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Overall results suggested that biosolids land application in this setting, at the rates used, posed little risk of environmental degradation. Ippolito et al (2009Ippolito et al ( , 2014 focused on the fate and transport of Cu and Zn in Meadow Springs Ranch biosolids-amended systems studied by and Sullivan, Stromberger, Paschke, and Ippolito (2006) because Cu and Zn are the greatest biosolids-borne metals applied to the Meadow Springs Ranch. The authors addressed potential downward transport mechanisms and protection against groundwater contamination from both metals.…”
Section: Core Ideasmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall results suggested that biosolids land application in this setting, at the rates used, posed little risk of environmental degradation. Ippolito et al (2009Ippolito et al ( , 2014 focused on the fate and transport of Cu and Zn in Meadow Springs Ranch biosolids-amended systems studied by and Sullivan, Stromberger, Paschke, and Ippolito (2006) because Cu and Zn are the greatest biosolids-borne metals applied to the Meadow Springs Ranch. The authors addressed potential downward transport mechanisms and protection against groundwater contamination from both metals.…”
Section: Core Ideasmentioning
confidence: 99%
“…Ippolito et al. (2009, 2014) focused on the fate and transport of Cu and Zn in Meadow Springs Ranch biosolids‐amended systems studied by Sullivan, Stromberger, and Paschke (2006) and Sullivan, Stromberger, Paschke, and Ippolito (2006) because Cu and Zn are the greatest biosolids‐borne metals applied to the Meadow Springs Ranch. The authors addressed potential downward transport mechanisms and protection against groundwater contamination from both metals.…”
Section: Colorado Ecosystems That Have Received Biosolidsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the application process of Cu-contaminated BR, the migration mechanism of Cu in saline-alkali soil (SAS) has yet to be explored. The application of synchrotron radiation [1], electron microscope [3], X-ray absorption spectroscopy [4] and other physical research methods [5,6] in the field of soil environment provides more intuitive research methods for the occurrence and migration of heavy metals in soil. In the process of sludge improvement of farmland soil, the decomposition of organic matter was found to be the key factors of Cu [7][8][9].…”
Section: Introductionmentioning
confidence: 99%